2022
DOI: 10.1007/s00381-022-05634-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the risk factors of post-operative seizure in pediatric patients with hydrocephalus undergoing endoscopic third ventriculostomy

Abstract: Methods: Data of pediatric patients with hydrocephalus who were treated with ETV from October 1, 2015, to November 31, 2021, were retrospectively analyzed. Basic demographic characteristics, etiology of hydrocephalus, surgical details, and laboratory measurements were collected. An early postoperative seizure was de ned as the occurrence of at least one clinical seizure within 24 h of ETV.Results: A total of 50 participants were included in the study, of whom 5 (10.00%) cases were in postoperative epilepsy gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Recently, animal research showed a certain relationship between magnesium homeostasis and acute or chronic seizures 13 . Likewise, lower serum calcium concentrations was reported to be associated with a higher risk of epilepsy 9,10,14 . As we know, hypomagnesaemia can cause serum calcium levels to decline by affecting the synthesis or secretion of parathyroid hormone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, animal research showed a certain relationship between magnesium homeostasis and acute or chronic seizures 13 . Likewise, lower serum calcium concentrations was reported to be associated with a higher risk of epilepsy 9,10,14 . As we know, hypomagnesaemia can cause serum calcium levels to decline by affecting the synthesis or secretion of parathyroid hormone.…”
Section: Introductionmentioning
confidence: 99%
“… 13 Likewise, lower serum calcium concentrations was reported to be associated with a higher risk of epilepsy. 9 , 10 , 14 As we know, hypomagnesaemia can cause serum calcium levels to decline by affecting the synthesis or secretion of parathyroid hormone. In addition, low levels of serum calcium, together with low magnesium levels, can lead to membrane hyperexcitability in neurons, which has been found to be strongly related to seizures in both children and adults.…”
Section: Introductionmentioning
confidence: 99%